Observations on Pluteaceae in Vietnam. 2. One new record and ten new species of Pluteus - Malysheva, Ekaterina; Malysheva, Vera; Alexandrova, Alina; Morozova, Olga (Phytotaxa, 2020)
Fourteen specimens of Pluteus all collected in tropical forests of Vietnam were studied using morphological and molecular approaches. Pluteus subcervinus, is noted as a new record for Vietnam, and one collection appears to be close to P. velutinus, but not phylogenetically identical. One species of Pluteus from sect. Pluteus with metuloid pleurocystidia and pileipellis as a cutis (P. olivaceofibrillosus), one species from sect. Hispidoderma with non-metuloid cystidia and pileipellis as a hymeniderm (P. pallidosquamulosus), and eight species from sect. Celluloderma with non-metuloid cystidia and pileipellis organized as a cutis, an epithelium or a hymeniderm (P. varius, P. atypicus, P. castaneorugosus, P. flavidus, P. squamulososulcatus, P. podospilloides, P. pygmaeus and P. brunneovelutinus) are proposed as new. Descriptions of their macro- and microscopic features with a discussion of similar taxa are given. Their taxonomic positions were confirmed using DNA data.